Best practices to impart clinical skills during preclinical years of medical curriculum - Pradeep Kumar Sahu; Vijay Kumar Chattu; Aishwarya Rewatkar; Sateesh Sakhamuri (Wolters Kluwer Medknow Publications, 2019)
Globally, health is regarded as a booming industry with greater stress being laid on high quality, accountability, and transparency. Traditional medical curricula rely primarily on clerkships during the clinical period of study to train clinical skills, while the preclinical period is mainly used to teach the basic sciences. In recent years, the early introduction of clinical skills training has received increased attention. This review aims to identify and summarize teaching approaches of clinical skills for medical students during preclinical years, namely, (1) framing objectives (2) learning activities, and (3) evaluation strategies. Although the clinical tutor's role is to ensure that students receive effective preclinical skills through different modes of learning (lectures, presentations, and problem-based learning), the role of advanced technologies, namely, simulation-based learning platforms and gamification are found to be very successful. To improve the communication skills, there is strong evidence in support of role plays, and similarly, for enhancing observation skills, an introduction of fine arts in clinical skills training was found to be very useful. Medical schools worldwide should give high priority to conduct faculty development programs on various aspects of training and teaching modalities, evaluation strategies, and improving the evaluation of various clinical skills. Students should be provided with sufficient learning opportunities including a well-equipped clinical skills laboratory and individual attention, and constructive feedback should be given to students for building their confidence level during their learning process.